Crystallization Studies of Lithium Borosilicate Glasses - Qazi, Pervez Iqbal; Shah, Wajid Ali; Shaheen, Fadia (Biological Sciences - PJSIR, 2006)
. Lithium borosilicate ternary system is analogous to the most commercially exploited Na O-B O -SiO sys- 2 2 3 2 tem. The tendency towards liquid-liquid immiscibility is enhanced when sodium is replaced by lithium, which facili- tates the crystallization process. In the present work, three compositions of lithium borosilicate glasses were formu- 2 2 lated and melted by varying the mol percent ratio of SiO and Li O. The glasses were subsequently subjected to crystallization by isothermal heat-treatments at identical temperatures for various specific time durations. The crystal growth was found to be linear and the rate of crystallization was dependent on SiO /Li O ratio. The phases that 2 2 developed during heat-treatments were identified using XRD